Pengaruh Inflasi, Saham Syariah, Sukuk, Reksadana Syariah Dan Asuransi Syariah Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2015-2022 - Dermawan Has Putra; Shafa Shafa; Anwaril Hamidy (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
As a developing country, Indonesia needs qualified economic instruments to increase national economic growth by at least 7%. On the other hand, Indonesia is one of the nations with the most advanced Islamic economy. It an excellent opportunity for Indonesia to enhance national economic growth through Islamic Stocks, Sukuk, Islamic Mutual Funds, and Islamic Insurance. However, Indonesia has not taken full advantage of these conditions, as the GDP has stagnated at 5% for the past eight years. In addition, several other factors, such as inflation, might affect national economic growth. This research aimed to determine the effect of inflation, Islamic stocks, Sukuk, Islamic mutual funds, and Islamic insurance on Indonesia’s economic growth in 2015-2022. This research employed quantitative methods. The data was collected using the Time Series technique in 2015-2022, which comprised 95 data. The data were analyzed by descriptive statistics, classical assumption test and multiple linear regression with the SPSS version 26. Partially, the result indicates that inflation did not significantly affect Indonesia’s economic growth. Islamic stocks significantly affected Indonesia’s economic growth. Sukuk significantly affected Indonesia’s economic growth. Islamic mutual funds did not significantly affect Indonesia’s economic growth. Islamic insurance significantly affected Indonesia’s economic growth. Simultaneously, inflation, Islamic stocks, sukuk, Islamic mutual funds and Islamic insurance significantly affected Indonesia’s economic growth.